RELATIONSHIP BETWEEN SPERM DNA FRAGMENTATION INDEX AND CONVENTIONAL SEMEN PARAMETERS IN MALE PATIENTS WITH INFERTILITY (Vietnam Journal of Community Medicine, 2022)
Objectives: To determine the relationship between sperm chromatin dispersion test (SCD)parameters (DNA fragmentation index - DFI) and conventional semen parameters in male patientswith infertility.Subjects and methods: A cross-sectional descriptive study was performed on 150 semensamples of male patients by masturbation at the Center for Assisted Reproduction and Andrology -Phu Tho Obstetrics & Pediatrics Hospital. Evaluation of semen parameters according to WHO(2021) and determination of sperm DNA fragmentation index by SCD method.Results: A significant negative association between DFI with: Sperm density (r = -0.405,p
Keywords: Halosperm, Sperm DNA fragmentation, infertile men, Sperm chromatin dispersion test.